An Equilibrium Model with Restricted Stock Market Participation - Basak, Suleyman; Cuoco, Domenico (Review of Financial Studies, 1998)
This article solves the equilibrium problem in a pure-exchange, continuous-time economy in which some agents face information costs or other types of frictions effectively preventing them from investing in the stock market. Under the assumption that the restricted agents have logarithmic utilities, a complete characterization of equilibrium prices and consumption/ investment policies is provided. A simple calibration shows that the model can help resolve some of the empirical asset pricing puzzles. It is well documented that even in well-developed capital markets, a large fraction of households does not participate in the stock market. For example, Mankiw and Zeldes (1991) report that 72.4 % of the households in a representative sample from the 1984 Panel Study of Income Dynamics held no stocks at all. 1 These households earned 62 % of the aggregate disposable income and accounted for 68 % of aggre-We thank Steve Shreve for several conversations on this topic and Kerry